Edukasi Hukum Upaya Pencegahan Dan Penanggulangan Tindak Kekerasan Di Satuan Pendidikan Madrasah Aliyah Al-Washliyah Binjai Serbangan - Suriani Suriani; Zuwairiah Harmika; Lica Adila; Firma Nduru (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Violence in the educational environment is a serious problem that affects student well-being and academic achievement as well as interfering with the learning process. This dedication aims to see the potential and implement prevention and rejection strategies in schools. In this increasingly complex world, education is crucial to building a positive personality, knowledge, and attitude towards a variety of social challenges and risky behaviors. We involve students, teachers, parents, and local communities in designing and implementing a variety of relevant and sustainable prevention and prevention activities through collaborative and participatory approaches. To find problems, create solutions, and measure the effect of interventions, surveys and interviews are used. The results of this dedication show that an inclusive, educational, and responsive environment to the needs of students and the surrounding community is crucial. This dedication shows that prevention and rejection integrated into curricula and extracurricular activities can be a key capital in increasing social resilience and reducing the risk of negative behaviour among adolescents. In conclusion, educational institutions, communities, and other stakeholders must work together to build a safe, healthy, resilient environment. The study helps practitioners, policymakers, and researchers design and implement successful and sustainable prevention programmes in educational institutions.